Вредные привычки и их последствия - Акопов Иван Эмануилович (Книжное издательство, 1981)
Экземпляры: КХ (20120228) / Инвентарный номер: 0255461 / Цена: 0.15 / Сис.шифр: 613 / Авт.знак: А 40 / ГРНТИ: 76 / ББК: 5